2017
DOI: 10.1177/1178223417694520
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Adherence to Aromatase Inhibitor Therapy among Breast Cancer Survivors: An Application of the Protection Motivation Theory

Abstract: The purpose of this observational study was to determine if the Protection Motivation Theory could predict and explain adherence to aromatase inhibitor (AI) therapy among breast cancer survivors. Purposive sampling was used to identify 288 survivors who had been prescribed AI therapy. A valid and reliable survey was mailed to survivors. A total of 145 survivors completed the survey.The Morisky scale was used to measure adherence to AI. The survivors reported a mean score of 6.84 (±0.66) on the scale. Nearly 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 40 publications
1
21
0
1
Order By: Relevance
“… 42 Negative and positive emotions regarding therapy were related to decreased and increased adherence, respectively, 35 , 68 and perceived importance of therapy was related to increased adherence. 61 Karmakar 69 found that coping appraisal, defined as the effectiveness of taking HT and self-efficacy in ability to take HT, minus the costs of taking HT, was associated with increased odds of adherence. Four studies found no effects of necessity beliefs on adherence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 42 Negative and positive emotions regarding therapy were related to decreased and increased adherence, respectively, 35 , 68 and perceived importance of therapy was related to increased adherence. 61 Karmakar 69 found that coping appraisal, defined as the effectiveness of taking HT and self-efficacy in ability to take HT, minus the costs of taking HT, was associated with increased odds of adherence. Four studies found no effects of necessity beliefs on adherence.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies found a positive relationship between perceived self-efficacy for medication taking and adherence. 27 , 29 , 69 …”
Section: Resultsmentioning
confidence: 99%
“…13 Another study reported that more than 30% of AI users were non-adherent to AI by the third year after diagnosis and the non-adherence rate reached 53.33% after 5 years from diagnosis. 14 Studies published from 2008 to 2012 suggested the use of omega-3 fatty acids, glucosamine sulphate, nonsteroidal anti-inflammatory drugs (NSAIDs), codeine/ acetaminophen and change to another AI therapy to manage AIA. 5 15 However, these AIA treatment algorithms were based on the management of peripheral pain 15 and information from literature and anecdotal experience of oncologists, 5 not randomised controlled trials (RCTs) on AIA.…”
Section: Introductionmentioning
confidence: 99%
“…Threat appraisal can be defined as the survivors’ perceptions of the health threat, constitutes the combination of the survivors’ perceived vulnerability and perceived severity. 18 Both strategies from PMT were applied to the pictorial diary handbook (PDHB) program. Mobile phone text messaging has been shown to reduce glycated hemoglobin, 19 and participants are willing to pay for such programs, including the mobile phone use and the cost of short message service (SMS), for diabetes interventions in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%